2022
DOI: 10.1515/jpm-2021-0363
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal mortality audits and reporting of perinatal deaths: systematic review of outcomes and barriers

Abstract: Background Perinatal deaths are a devastating experience for all families and healthcare professionals involved. Audit of perinatal mortality (PNM) is essential to better understand the factors associated with perinatal death, to identify key deficiencies in healthcare provision and should be utilised to improve the quality of perinatal care. However, barriers exist to successful audit implementation and few countries have implemented national perinatal audit programs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Publications of outcomes of systematically organised perinatal audits are rare. A systematic review of Gutman et al [23] revealed 20 articles from 2000 and onwards evaluating perinatal mortality audits. Timely and adequate monitoring of foetal and maternal conditions were common improvable factors in cases of perinatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Publications of outcomes of systematically organised perinatal audits are rare. A systematic review of Gutman et al [23] revealed 20 articles from 2000 and onwards evaluating perinatal mortality audits. Timely and adequate monitoring of foetal and maternal conditions were common improvable factors in cases of perinatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These lessons relate to findings from other studies examining the history of implementation of MPDSR processes. 3,[71][72][73] More operational research and in-depth studies, especially from LMICs, will be needed to better understand implementation history and practice in different contexts. 71,74 Factors influencing implementation of MPDSR in LMICs have been identified and examined in the literature, 13 including for South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty of impact of the current perinatal audit program on mortality reduction in South Africa 21 does not necessarily indicate failure of the program, especially when global systematic reviews on the impact of MPDSR rest on too few studies. 73,74,83 Quality of practice or "functional PPIP" is necessary for health system improvements. 22 A complementary article of this research presents evidence that there are other benefits to the perinatal audit program beyond mortality outcomes, such as skills development, individual and collective motivation, and improved teamwork and dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from SSA highlight that it is very frequent that some depressed but living fetuses with a possible heartbeat do not receive resuscitation maneuvers and are prompt classified as stillbirths [1,66]. This is supported by a systematic review of sixteen hospitals and community-based perinatal mortality studies [67,68].…”
Section: Discussionmentioning
confidence: 99%